MAGNETIC FORCE MICROSCOPE IMAGE EVALUATION OF MAGNETIC IRON OXIDE FLOPPY DISC WITH VARIOUS LIFT HEIGHTS - Nanda Shabrina; Mardiyanto Mardiyanto; Abu Khalid Rivai (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
Magnetic Force Microscope Image Evaluation of Magnetic Iron Oxide Floppy Disc with Various Lift Heights. One of the advantages of Scanning Probe Microscopes (SPM) or better known as the Atomic Force Microscope (AFM) is its ability to